1969
DOI: 10.1111/j.1399-3054.1969.tb07420.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Uptake of Zinc by Fontinalis antipyretica

Abstract: Ilie liile of uptake, the effect.s of carrier ions, temperature, tight intensity and «iiiiiti Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…The first stage (exchange adsorption) corresponds to a rapid surface binding; a large amount of zinc is taken up in this stage and it is limited to the Donnan-free-space of the cell wall [17]. The second stage is slower and it is the intracellular diffusion (penetration into the protoplast including the cell organelles) that governs the process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first stage (exchange adsorption) corresponds to a rapid surface binding; a large amount of zinc is taken up in this stage and it is limited to the Donnan-free-space of the cell wall [17]. The second stage is slower and it is the intracellular diffusion (penetration into the protoplast including the cell organelles) that governs the process.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metal accumulation in bryophytes has been studied by several authors [16,17] to elucidate the uptake and/or release mechanisms and the uptake rate from metal-enriched solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors [22,23] suggested, from batch experiments, that two or three stages could be identifiable during metal uptake by plant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Des études portant sur l'influence des ions Ca ++ (PICKERING et PUIA, 1969, SAY et WHITTON, 1983, WEHR, 1983 et Mg ++ (BROWN et BECKETT, 1985, WELLS et BROWN, 1987, 1990 Des études en laboratoire sont maintenant nécessaires afin de mieux isoler l'action de quelques paramètres sur l'accumulation et l'élimination des métaux par les mousses. Ainsi, cette étude vise à évaluer les effets du temps d'exposition, de la concentration de Cd dans l'eau, de l'espèce de mousses, mais plus particulièrement de la dureté de l'eau sur l'accumulation et l'élimination de Cd réalisées par deux mousses aquatiques.…”
Section: -Introductionunclassified